2012
DOI: 10.1002/eji.201142104
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity against M2 muscarinic acetylcholine receptor induces myocarditis and leads to a dilated cardiomyopathy‐like phenotype

Abstract: Patients with dilated cardiomyopathy (DCM) often have autoantibodies against cardiac antigens including the M 2 muscarinic acetylcholine receptor (M 2 R). To elucidate the role of autoimmunity against M 2 R in disease development, we induced an immune response against M 2 R by adoptive transfer into Rag2 -/-mice of splenocytes from M 2 R -/-mice immunized with a recombinant M 2 R protein. T lymphocytes transiently infiltrated the heart in recipient mice followed by morphological changes in cardiomyocytes. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…However, the pathophysiological roles of M 2 -AA in the development of DCM need further exploration. In the present model, long-term presence of M 2 -AA can lead to DCM-like morphological changes especially the right ventricular dilation, which is consistent with previous reports [5]. In addition, M 2 -AA can gradually deteriorate cardiac systolic and diastolic function.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the pathophysiological roles of M 2 -AA in the development of DCM need further exploration. In the present model, long-term presence of M 2 -AA can lead to DCM-like morphological changes especially the right ventricular dilation, which is consistent with previous reports [5]. In addition, M 2 -AA can gradually deteriorate cardiac systolic and diastolic function.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study demonstrated that M 2 -AA could recognize the second extracellular loop of the M 2 muscarinic receptor (M 2 AChR-el2) and stimulate the muscarinic receptor on rats’ heart membrane [4]. Recent studies also indicated that M 2 -AA was responsible for DCM-like morphological changes in mice that were immunized with M 2 receptor for 8 weeks [5]. However, whether long term exposure to M 2 -AA can worsen cardiac function during progression of DCM remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…M 2 R-AAbs extracted from DCM patients induced a significant decrease in Ca 2+ currents [39], negative chronotropic effect in vitro [37] and supraventricular arrhythmia ex vivo [38] which were blocked by M 2 antagonist [38,39] or a synthetic peptide derived from the second extracellular loop of M 2 R [38]. M 2 R-AAbs were also detected along with the induction of DCM-like morphology in the heart of mice receiving adoptive transfer of splenocytes from M 2 R null mice immunized with synthetic M 2 R peptide [40]. In addition, AAbs from these mice induced a significant decrease in Ca 2+ currents in ventricular cardiomyocytes, which was blocked by M 2 R antagonists or synthetic M 2 R peptides [40].…”
Section: Dilated Cardiomyopathy: a Possible Autoimmune Originmentioning
confidence: 99%
“…M 2 R-AAbs were also detected along with the induction of DCM-like morphology in the heart of mice receiving adoptive transfer of splenocytes from M 2 R null mice immunized with synthetic M 2 R peptide [40]. In addition, AAbs from these mice induced a significant decrease in Ca 2+ currents in ventricular cardiomyocytes, which was blocked by M 2 R antagonists or synthetic M 2 R peptides [40]. Clinically the presence of M 2 R-AAbs was strongly and independently associated with the comorbidity of atrial fibrillation [38], and may serve as an independent predictor for the recurrence of atrial fibrillation after catheter ablation [41].…”
Section: Dilated Cardiomyopathy: a Possible Autoimmune Originmentioning
confidence: 99%
“…Autoimmunity has been considered as one of major causes for idiopathic DCM (23) , and high titers of autoantibodies (M 2 -AA) against the second extracellular loop of the M 2 muscarinic receptor (M 2 AChR-el2) has been found in serum of patients with idiopathic DCM (24) . Animal models have been established by immunizing rats (25 , 26) or mice (27) with synthetic M 2 AChR-el2 peptide to induce DCM-like morphological changes in the animals’ heart. M 2 AChR-el2-immunized rat heart showed decreased systolic and diastolic function with swollen and damaged mitochondria (26) .…”
Section: Mitochondrial Defects In Experimental Models Of Cardiomyopatmentioning
confidence: 99%